2014
DOI: 10.1007/s11356-014-2508-5
|View full text |Cite
|
Sign up to set email alerts
|

Nano-silver in drinking water and drinking water sources: stability and influences on disinfection by-product formation

Abstract: Nano-silver is increasingly used in consumer products from washing machines and refrigerators to devices marketed for the disinfection of drinking water or recreational water. The nano-silver in these products may be released, ending up in surface water bodies which may be used as drinking water sources. Little information is available about the stability of the nano-silver in sources of drinking water, its fate during drinking water disinfection processes, and its interaction with disinfection agents and disi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 21 publications
0
31
2
Order By: Relevance
“…37 This conclusion is in direct contrast to the findings of the present View Article Online study, which indicated a significant increase in chloroform production in the presence of citrate coated AgNPs. 37 This conclusion is in direct contrast to the findings of the present View Article Online study, which indicated a significant increase in chloroform production in the presence of citrate coated AgNPs.…”
Section: Potential Effects Of Nanomaterials Coatingscontrasting
confidence: 99%
See 1 more Smart Citation
“…37 This conclusion is in direct contrast to the findings of the present View Article Online study, which indicated a significant increase in chloroform production in the presence of citrate coated AgNPs. 37 This conclusion is in direct contrast to the findings of the present View Article Online study, which indicated a significant increase in chloroform production in the presence of citrate coated AgNPs.…”
Section: Potential Effects Of Nanomaterials Coatingscontrasting
confidence: 99%
“…37 Citrate coatings are commonly used in studies investigating nanoparticle behavior as citrate is often used to reduce metal salts to nanoparticles in industrial applications before the particles are coated with another substance. It is hypothesized that the citrate coating plays a crucial role in the reactions enhancing chloroform formation, given that a similar study using PVP coated AgNPs observed no enhanced chloroform formation.…”
Section: Conclusion Environmental Implicationsmentioning
confidence: 99%
“…119 Silver for water disinfection Silver (Ag) has been known to have antibacterial properties as Roman times and in the modern era it has been used extensively for water disinfections, including potable water. 120 The remarkable antimicrobial property of silver is mainly attributed to its strong binding with disulfide (S-S) and sulfhydryl (-SH) groups found in the proteins of microbial cell walls, which disrupts the normal metabolic processes leading to cell death. 121 Silver is considered as an alternative to the harmful chlorine-based water disinfection processes and used widely across the world, even extending its use up to the space shuttles.…”
Section: Ozone Disinfectionmentioning
confidence: 99%
“…Nanosilver is increasingly being used in consumer products from washing machines and refrigerators to other devices. Silver nanoparticles are known to be excellent antimicrobial agents, and therefore they can be used as alternative disinfectant agents for the disinfection of drinking water or recreational water [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%